Study of the Effect of Dissolved Oxygen Concentration on Gold Recovery Leaching at PT Indo Muro Kencana - Putri GF, Frideni Yushandiana; Pauru', Wilson; ., Sulaeman (Equilibrium Journal of Chemical Engineering, 2024)
Gold is a very important metal in human life. Most gold is processed using the sodium cyanide (NaCN) leaching method. Maximizing the leaching recovery can be done by optimizing the leaching process parameters, one of which varies the concentration of dissolved oxygen (DO). Oxygen is added to oxidize gold atoms (Au) into cations (Au+) which will then react with cyanide ions (CN-) to form the aurocyanid complex anion Au(CN)2- dissolved in cyanide solution. This study aims to investigate the best method between the use of O2, H2O2, and Aachen reactor in generating dissolved oxygen concentration to oxidize valuable metals. From the experimental results, which method can produce higher leaching recovery will be seen. Based on this study, the dissolved oxygen variation derived from oxygen injection (O2) obtained a percent recovery of 92.5% Au and 80.5% Ag, hydrogen peroxide (H2O2) achieved a percent recovery of 92.5% Au and 79.9% Ag, and Aachen sheared (Aachen reactor) with a percent recovery of 95% Au and 81.9% Ag.Keywords:Gold, Leaching, Dissolved Oxygen, Percent Recovery, Aachen Reactor